2012
DOI: 10.4104/pcrj.2012.00046
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry: an essential tool for screening, case-finding, and diagnosis of COPD

Abstract: EditorialsThe Global Alliance against Chronic Respiratory Diseases estimates that there are 210 million cases of chronic obstructive pulmonary disease (COPD) globally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 12 publications
0
10
0
2
Order By: Relevance
“…Different questionnaires have been developed for COPD case finding in primary care based on variables associated with increased or decreased risk of COPD . Recently, Stanley et al ., using the COPD Diagnostic Questionnaire, found that it did not perform well in identifying people with COPD when compared with spirometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different questionnaires have been developed for COPD case finding in primary care based on variables associated with increased or decreased risk of COPD . Recently, Stanley et al ., using the COPD Diagnostic Questionnaire, found that it did not perform well in identifying people with COPD when compared with spirometry.…”
Section: Discussionmentioning
confidence: 99%
“…However, extrapolation of the results to 1 year suggests that opportunistic approaches may be more efficient. Several studies have looked at developing screening tools to select persons at risk for further spirometric investigation . The simpler and more accurate the screening tool, the more useful for identifying patients for spirometry diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Formal questionnaires designed to improve the efficiency and accuracy of a COPD diagnosis have been shown to perform well when used to select patients for diagnostic spirometry. 17 The COPD Diagnostic Questionnaire, 18 the Lung Function Questionnaire, 19 and the COPD Assessment Test 20 are 3 examples in which specific cut points (based on questionnaire score) identified patients whose subsequent spirometry confirmed a diagnosis of COPD. Some patients have symptoms that result in questionnaire scores consistent with COPD, although their spi-rometry values are above the usual thresholds for airway obstruction.…”
Section: Case Finding and Screening For Copdmentioning
confidence: 99%
“…Entre estos dispositivos cabe destacar a aquellos con capacidad para la medición del cociente FEV 1 /FEV 6 , por ser éste el parámetro clave para el diagnóstico de EPOC. Estos dispositivos simplifican el procedimiento para la obtención del cociente FEV 1 /FEV 6 respecto a la espirometría forzada convencional y pueden contribuir a la reducción de la variabilidad entre centros de salud respecto a la disponibilidad de pruebas para el diagnóstico de EPOC 138 .…”
Section: Detección Precoz De La Enfermedadunclassified
“…Esta recuperación fue menor en los pacientes que no dejaron de fumar hasta que la enfermedad había progresado hasta un nivel de mayor de gravedad. Estos datos sugieren que los pacientes con EPOC pueden modificar la progresión de la enfermedad dejando de fumar, y los máximos efectos se observan cuando la intervención se produce en una fase precoz136 .Por lo expuesto anteriormente, una de las consecuencias del infradiagnóstico es el retraso en la intervención sobre los factores de riesgo, principalmente el consumo de tabaco138 . Para realizar la intervención sobre los factores de riesgo existen distintos niveles.…”
unclassified